PITTING CORROSION OF TiN-COATED STAINLESS STEEL IN 3 % NaCl SOLUTION - (:unkn) unknown (INST ZA KOVINSKE MATERIALE I IN TEHNOLOGIE, 2015)
TiN coatings deposited by arc PVD were characterized by XRD and SEM. In-situ measurements of the corrosion of the substrate and the TiN-coated substrate were made using the corrosion potential (Cor.Pot.), the polarization resistance (PR) method and electrochemical impedance spectroscopy (EIS) in a 3 % NaCl solution as a function of the immersion time. The semiconductor scale formed on the TiN was identified using a Mott-Shottky analysis as an n-type semiconductor with a flat band potential of -0.83 V vs. SCE. The TiN coating (0.5 mu m thick) consisted of cubic TiN exhibiting columnar grains, pin holes, voids and porosities. The pitting corrosion of the TiN, observed visually between I h and 2 h, was captured by EIS and PR. The electrical circuit (EC) model used for the EIS data supported the degradation of the coating through pitting corrosion, in agreement with the visual observations. The corrosion resistance (polarization resistance) determined by the polarization resistance method (R-p) and the EIS (R-total) decreased suddenly during the pitting corrosion. The corrosion resistance of the TiN-coated substrate was greater than the corrosion resistance of the substrate during the approximately 24 h of exposure.
Keywords: stainless steel; TiN; coating; EIS; polarization resistance; pitting corrosion; ELECTROCHEMICAL IMPEDANCE SPECTROSCOPY; MACHINING PERFORMANCE; AQUEOUS-SOLUTION; BEHAVIOR; COATINGS; CRN; RESISTANCE; TIALN